Watching Microwave‐Induced Microscopic Hot Spots via the Thermosensitive Fluorescence of Europium/Terbium Mixed‐Metal Organic Complexes. Issue 6 (29th December 2021) - Zhao, Zhenyu; Shen, Xi; Li, Hong; Liu, Kai; Wu, Haoyu; Li, Xingang; Gao, Xin
Abstract: The hypothesis of microscopic hot spots is widely used to explain the unique microwave (MW) effect in materials science and chemical engineering, but it has not yet been directly measured. Herein we use Eu/Tb mixed‐metal organic complexes as nano thermometers to probe the intrinsic temperature of MW‐absorbing particles in MW fields based on the thermosensitive fluorescent spectra. According to the measurements of the temperature gradient at the solid/liquid interphase, we derive an MW‐irradiated energy transfer model to predict the extent of microscopic hot spots. The fluorescence results agree with the model predictions that the MW‐induced temperature gradient can be enlarged by increasing MW intensity, as well as the dielectric loss and size of particles. Conversely, the increase in the thermal conductivity and the dielectric loss of the liquid lowers the temperature gradient. This study enables control of MW‐assisted synthesis and MW‐responsive techniques. Abstract : Microwave‐induced micro‐hot spots were detected in liquid solutions through fluorescence thermometers attached on microwave‐absorbing carbon particles. The fluorescent experiments confirmed the established microwave‐irradiated energy‐transfer model, whose results can guide precise control and optimization of conditions in microwave chemistry.